2012
DOI: 10.1124/dmd.112.046342
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism and Quantification of [18F]DPA-714, a New TSPO Positron Emission Tomography Radioligand

Abstract: ]DPA-714 were investigated in rats, baboons, and humans. Whole-body PET experiments showed a high uptake of radioactivity in the kidneys, heart, liver, and gallbladder. The liver was a major route of elimination of [ 18 F]DPA-714, and urine was a route of excretion for radiometabolites. In rat and baboon plasma, high-performance liquid chromatography (HPLC) metabolic profiles showed three major radiometabolites accounting for 85% and 89% of total radioactivity at 120 minutes after injection, respectively. Rat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 65 publications
(53 citation statements)
references
References 28 publications
2
50
1
Order By: Relevance
“…Our analyses showed that equilibrium was attained by 60 min, suggesting that acquisition time can be reduced to 60 min in clinical trials. Moreover, the small increase in V T between 60 and 90 min suggests that radiometabolites potentially entering the brain do not substantially contribute to V T , as previously described (23). Indeed, we recently showed that one 18 F-DPA-714 radiometabolite contributes to about 15% of brain radioactivity after 120 min in rats.…”
Section: Discussionsupporting
confidence: 62%
“…Our analyses showed that equilibrium was attained by 60 min, suggesting that acquisition time can be reduced to 60 min in clinical trials. Moreover, the small increase in V T between 60 and 90 min suggests that radiometabolites potentially entering the brain do not substantially contribute to V T , as previously described (23). Indeed, we recently showed that one 18 F-DPA-714 radiometabolite contributes to about 15% of brain radioactivity after 120 min in rats.…”
Section: Discussionsupporting
confidence: 62%
“…While the fluorine-18-labeled tracers, [ 18 F]PBR102, [ 18 F]PBR111, [ 18 F]PBR146, and [ 18 F]DPA-714, have good brain penetration and kinetics, their main pitfall arises from their labeling positions. Metabolism of these tracers results in cleavage of the radioactive label [21, 22] and the formation of non-specifically binding radiometabolites. Despite these shortcomings, the extensive use of these tracers in both preclinical and clinical studies, together with the ongoing development of more metabolically stable analogues [23, 24], further underpins the importance of this motif.…”
Section: Introductionmentioning
confidence: 99%
“…To investigate the metabolism of [ 11 C]PBB3 mediated by cytochrome P450 enzymes (CYPs), we performed an in vitro metabolite analysis of [ 11 C]PBB3 using human or mouse liver microsomes and an NADPH regeneration system as an activator of oxidative reactions by CYPs, as previously described, with minor modifications [10,11]. stopped by the addition of an equal volume of acetonitrile.…”
Section: Human and Mouse Liver Microsomesmentioning
confidence: 99%